2008
DOI: 10.1097/scs.0b013e31816ae746
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dynamic Magnetic Resonance Imaging in Assessing Velopharyngeal Insufficiency During Phonation

Abstract: In cleft palate cases with delayed diagnosis, appropriate application of muscle repair will be sufficient for anatomic repair of VPI without any extra procedures. In addition, dynamic magnetic resonance imaging is an objective, noninvasive, reliable, and effective modality that may be used in the diagnosis and treatment of VPI without any extra investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 16 publications
0
41
0
Order By: Relevance
“…Most studies evaluated velopharyngeal function with MRI in healthy volunteers [4][5][6]12]. The few short studies in which the subjects had VPI concerned children older than those in our study [5,11,15]. For example, Beer et al [7] studied velopharyngeal function with near real-time dynamic MRI using a turbo spin echo sequence in seven patients and a healthy volunteer, in comparison to videofluoroscopy.…”
Section: Discussionmentioning
confidence: 84%
“…Most studies evaluated velopharyngeal function with MRI in healthy volunteers [4][5][6]12]. The few short studies in which the subjects had VPI concerned children older than those in our study [5,11,15]. For example, Beer et al [7] studied velopharyngeal function with near real-time dynamic MRI using a turbo spin echo sequence in seven patients and a healthy volunteer, in comparison to videofluoroscopy.…”
Section: Discussionmentioning
confidence: 84%
“…It can be suggested to be a pushing back maneuver as understood from the name, especially in the V-Y pushback operation. However, Atik et al 18 reported that there is no a true lengthening in this maneuver. Intraoperatively, an average of 9.5-mm lengthening was obtained in the technique reported in this study because of the rotation maneuver.…”
Section: Discussionmentioning
confidence: 95%
“…Wardill suggested pushing back the mucoperiosteal flaps to ensure palate elongation. 8 Using measurements obtained from dynamic MRI, Atik et al 11 reported that palate elongation was not ensured after V-Y pushback palatoplasty. Bae et al 12 reported that the intraoperative two-flap palatoplasty elongated the palate to a greater extent than the V-Y pushback in the incomplete cleft palate.…”
Section: Discussionmentioning
confidence: 99%
“…Within the historical development of cleft palate repair, each surgical technique has separated the nasal and oral cavities from one another. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] In addition to this basic surgical goal, several techniques have focused on improving the anatomical repair of the palate muscles. [1][2][3] Some techniques have been directed towards increasing the palate length, [4][5][6][7][8] whereas others have focused on both anatomical repair of the muscles and increasing the palate length.…”
mentioning
confidence: 99%